PERBANDINGAN EFISIENSI PADA INDUSTRI ASURANSI JIWA SYARIAH DAN KONVENSIONAL DENGAN DATA ENVELOPMENT ANALYSIS (DEA) - Foza Hadyu Hasanatina; Risanda Alirastra Budiantoro; Vicky Oktavia (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2020)
This study aims to anlyze and comparing the efficiency of Islamic Life Insurance and Conventional Life Insurance in Indonesia. This study uses a quantitative non-parametric approach with Data Envelopment Analysis (DEA) with the assumption of Constant Return to Scale (CRS) and Variable Return to Scale (VRS) with input and output orientation. The samples are 3 Islamic Life Insurance (full fledge) and 3 Conventional Life Insurance that comply with the specified sample criteria during 2012-2019. The input variables used ared cost of commissive, operational cost, total equity, while the output variables is the premi income, and investment revenue. The results of the study indicate that the average result of DEA analysis for the entire DMU (Decision Making Unit) has not been efficient. In Conventional Life Insurance, the value of economic efficiency by 64,82 percent, technically efficiency for72,22 percent, and scale efficiency 81,4 percent, while in Islamic Life Insurance, the value of economic efficiency by 17,26 percent, technically efficiency for 53,71 persen, and scale efficiency 47,41 percent. Source of inefficiency Conventional and Islamic Life Insurance company is the sacle of operations and management of input to output is not optimal.